EXPERTS FROM 16 COUNTRIES TO DISCUSS ON NONVIOLENT ALTERNATIVES IN DEALING WITH EXTREMISM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 19 September 2016 – Experts coming from 16 countries would gather here for three days beginning today to discuss on the topic of ‘Violent Extremism: Islam and Nonviolent Policy Alternatives.